Structure of the Q237W mutant of HhaI DNA methyltransferase: an insight into protein-protein interactions - Dong, Aiping (Walter De Gruyter, 2004)
We have determined the structure of a mutant (Q237W) of HhaI DNA methyltransferase, complexed with the methyl-donor product AdoHcy. The Q237W mutant proteins were crystallized in the monoclinic space group C2 with two molecules in the crystallographic asymmetric unit. Protein-protein interface calculations in the crystal lattices suggest that the dimer interface has the specific characteristics for homodimer protein-protein interactions, while the two active sites are spatially independent on the outer surface of the dimer. The solution behavior suggests the formation of HhaI dimers as well. The same HhaI dimer interface is also observed in the previously characterized binary (M.HhaI-AdoMet) and ternary (M.HhaI-DNA-AdoHcy) complex structures, crystallized in different space groups. The dimer is characterized either by a non-crystallographic two-fold symmetry or a crystallographic symmetry. The dimer interface involves three segments: the amino-terminal residues 2–8, the carboxy-terminal residues 313–327, and the linker (amino acids 179–184) between the two functional domains – the catalytic methylation domain and the DNA target recognition domain. Both the amino- and carboxy-terminal segments are part of the methylation domain. We also examined protein-protein interactions of other structurally characterized DNA MTases, which are often found as a 2-fold related ‘dimer’ with the largest dimer interface area for the group-β MTases. A possible evolutionary link between the Type I and Type II restriction-modification systems is discussed.